On the Eddy Current Losses in Metallic Towers - Ibrahim Mahariq; Svetlana Beryozkina; Huda Mohammed; Hamza Kurt (Center of Biomass & Renewable Energy, Diponegoro University, 2020)
The existence of magnetic field around high-voltage overhead transmission lines or low-voltage distribution lines is a known fact and well-studied in the literature. However, the interaction of this magnetic field either with transmission or distribution towers has not been investigated. Noteworthy it is to remember that this field is time-varying with a frequency of 50 Hz or 60 Hz depending on the country. In this paper, we studied for the first time the eddy currents in towers which are made of metals. As the geometrical structures of towers are extremely complex to model, we provide a simple approach based on principles of electromagnetism in order to verify the existence of power loss in the form of eddy currents. The frequency-domain finite difference method is adapted in the current study for simulating the proposed model. The importance of such a study is the addition of a new type of power loss to the power network due to the fact that some towers are made of relatively conductive materials.©2020. CBIORE-IJRED. All rights reserved